EDUKASI POLA MAKAN MENGGUNAKAN FOOD FREQUENCY QUESTIONNAIRE UNTUK PENCEGAHAN ANEMIA PADA REMAJA SMKN 05 JEMBER - Noerfadilah, Siti; Anggraeni, Ernawati; Handayani, Yuni (Politeknik Kesehatan Kemenkes malang, 2025)
Abstract: Background: Anemia is a medical condition characterized by a decrease in the number of red blood cells or hemoglobin levels in the body, so that the body cannot carry enough oxygen to the body's tissues. The cause of nutritional anemia is an imbalance between the consumption of iron sources that enter the body through insufficient food, this is influenced by diet. Anemia is one of the significant health problems among adolescents, especially in developing countries such as Indonesia. The goal: to increase adolescents' knowledge of proper diets so that they can prevent the occurrence of anemia. Method/stages of activity: This counseling is carried out in groups for each class on February 3, 2025, the target of this counseling is all students of the Department of Agricultural Quality Supervision at SMKN 05 Jember. Results: There was an increase in adolescents' knowledge about diet and the prevention of anemia. Conclusion: This activity is expected to provide information about the correct diet so that it can prevent the occurrence of anemia in adolescents. Key words: Diet, anemia, FFQ, adolescents, education